Ecological Risk in the Mountainous Metropolis of Chongqing: Historical Assessment and Flows of SSPs-RCPs Scenarios - WEI Mengyu; BIAN Hongyan; GAO Jie; ZHANG Lujin; JIA Runxi; LI Haolin; WANG Linyong (Shuitu Baochi Xuebao)
[Objective] Chongqing is a mega-metropolis located in the southwestern hilly region. The rising population and extensive economic development have led to rapid urban landscape ascent and expansion, resulting in a dual urban-rural and 3D spatial structure directly influencing the landscape's configuration, functionality, and sustainability. It is urgent to conduct spatiotemporal dynamics, sloping characteristics, and future scenario predictions for regional ecological risk. [Methods] Based on the use of land use/cover data from 1990-2020 and SSPs-RCPs (2035 and 2050), integrate the landscape ecological risk assessment model, portray the time and space dynamics and climbing laws of landscape ecological risks in Chongqing, predict the ecological risk and the flows of 5 SSPs-RCPs in 2035 and 2050. [Results] (1) The ecological risk index in Chongqing decreased from 0.14 in 1990 to 0.12 in 2020, indicating an overall improvement in habitat quality. Ecological risk was higher in natural landscapes (excluding forests), compared to artificial landscapes (cultivated land and built-up land), with urban landscapes showing an increasing ecological risk trend as urban-rural density decreased. Notably, grasslands exhibited an inverse ecological risk gradient. (2) The ecological risk was low in the northeast and southeast regions of Chongqing, including the Daba and Wuling Mountainous regions. In contrast, the southwestern region and hilly river valleys had high ecological risk. Low and moderately low-risk areas accounted for over 90% of the entire region. (3) Approximately 89.4% of landscapes were distributed in areas with a slope of ≥5°, and ecological restoration efforts in ecological barrier zones with a slope of >7.5° significantly reduced risks associated with steep slope erosion or rocky desertification. (4) Comparing ecological risks and spatial transition scenarios for 2035 and 2050 under different SSPs-RCPs, SSP1 demonstrated the most sustainable development pathway. The climbing and spreading of urban landscapes would lead to increased ecological risk, while effective risk reduction can be achieved through the management and restoration of the Yangtze River riparian zone, steep slope areas in the Wuling and Dalou Mountains, and mining sites. [Conclusion] The landscapes of the mountainous metropolis are sustainable which requires science-practice-policy collaborative governance, planning and management of scientific landscapes, and cross-department and public collaboration.